2012
DOI: 10.1371/journal.pone.0030365
|View full text |Cite
|
Sign up to set email alerts
|

Fgf Signaling is Required for Photoreceptor Maintenance in the Adult Zebrafish Retina

Abstract: Fibroblast growth factors (Fgf) are secreted signaling molecules that have mitogenic, patterning, neurotrophic and angiogenic properties. Their importance during embryonic development in patterning and morphogenesis of the vertebrate eye is well known, but less is known about the role of Fgfs in the adult vertebrate retina. To address Fgf function in adult retina, we determined the spatial distribution of components of the Fgf signaling pathway in the adult zebrafish retina. We detected differential expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 57 publications
(73 reference statements)
5
69
0
Order By: Relevance
“…For this analysis we used hsp70:dnfgfr1-egfp transgenic fish that harbor the hsp70 promoter driving expression of a dominant/negative Fgfr1-GFP fusion protein (dnFgfr1) (Lee et al, 2005). We found that conditional expression of dnFgfr1 suppressed MG proliferation in the injured retina (Figures 2G and 2H), which is consistent with that found when photoreceptors are damaged (Hochmann et al, 2012). …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For this analysis we used hsp70:dnfgfr1-egfp transgenic fish that harbor the hsp70 promoter driving expression of a dominant/negative Fgfr1-GFP fusion protein (dnFgfr1) (Lee et al, 2005). We found that conditional expression of dnFgfr1 suppressed MG proliferation in the injured retina (Figures 2G and 2H), which is consistent with that found when photoreceptors are damaged (Hochmann et al, 2012). …”
Section: Resultssupporting
confidence: 87%
“…Fgfs and their receptors are expressed in the INL of the zebrafish retina (Hochmann et al, 2012); however, the effects of Fgf signaling on MG proliferation are controversial (Hochmann et al, 2012; Qin et al, 2011). Therefore, we investigated Fgf signaling in our mechanical injury model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… * One study reports no effect of dnfgfr on progenitor proliferation following light damage and that fgf signaling is necessary for rod maintenance 115 , while the other study shows dnfgfr suppresses progenitor proliferation following light damage and that fgf signaling is necessary for rod and cone maintenance 123 . ! Notch signaling inhibits progenitor formation and proliferation in the injured retina 83 . …”
Section: Online `At-a-glance' Summarymentioning
confidence: 99%
“…Although injury-induced Müller-glia derived progenitors have the potential to regenerate all major retinal cell types, some reports suggest they predominantly regenerate ablated neurons 41,43,44 . Other studies suggest progenitors in the injured retina may retain a multipotent character regardless of the type of neuron ablated since ectopic neurons appear outside the injury site and are also found in uninjured retinas treated with a variety of growth factors and cytokines 2022,24 .…”
Section: Extrinsic Signals Regulating Lineage Specification Of Müllermentioning
confidence: 99%